2021
DOI: 10.1038/s41598-021-85023-w
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea is associated with impaired renal function in patients with diabetic kidney disease

Abstract: Obstructive sleep apnea (OSA) is a recognized risk factor for the development of diabetic kidney disease (DKD). Our objectives were to compare the urinary albumin–creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) of patients with DKD according to OSA severity, and to evaluate the contribution of sleep parameters to their renal function. In a multicenter, observational, cross-sectional study, 214 patients with DKD were recruited. After a sleep study, UACR and eGFR were measured, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A multicenter, observational, cross-sectional study using 214 DKD patients showed that UACR was higher in DKD with severe OSA relative to moderate OSA, mild OSA, or non-OSA subjects. Additionally, this study showed that the estimated GFR (eGFR) decreased in an OSA severity-dependent manner [90]. OSA-induced intermittent hypoxia and increased sympathetic nerve activity are associated with increased vascular complications, including endothelial damage and hypertension that leads to renal dysfunction [91].…”
Section: Sars-cov-2 Infection Exacerbates Diabetes-induced Renal Comp...mentioning
confidence: 84%
“…A multicenter, observational, cross-sectional study using 214 DKD patients showed that UACR was higher in DKD with severe OSA relative to moderate OSA, mild OSA, or non-OSA subjects. Additionally, this study showed that the estimated GFR (eGFR) decreased in an OSA severity-dependent manner [90]. OSA-induced intermittent hypoxia and increased sympathetic nerve activity are associated with increased vascular complications, including endothelial damage and hypertension that leads to renal dysfunction [91].…”
Section: Sars-cov-2 Infection Exacerbates Diabetes-induced Renal Comp...mentioning
confidence: 84%
“…However, previous studies have indicated that nap duration and OSA may also be linked to eGFR in both healthy individuals and those with diabetes [18,[20][21][22] . It is also found that OSA and nap time may affect sleep duration [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorder can lead to inflammation, oxidative stress, endothelial dysfunction, increased sympathetic tone, activation of the renin-angiotensin system, circadian timing dysfunction and subsequent systemic and intraglomerular pressure, which hereby adversely affects kidney function ( 24 26 , 31 , 32 ). Another possible explanation is the impact of sleep disorder on hypertension ( 33 , 34 ), diabetes ( 35 , 36 ), obesity ( 37 ), and metabolic syndrome ( 38 ), which were known to accelerate deterioration of kidney function.…”
Section: Discussionmentioning
confidence: 99%